Karakteristik Katarak Senilis pada Penderita Diabetes Mellitus - Chaeruni, Aulia; Amir, Suliati P.; Anoez , Azizah; Assagaf, Munjia; Maharani, Ratih Natasha (Universitas Pahlawan Tuanku Tambusai, 2025)
Cataracts are the leading cause of blindness in Indonesia. Around 77.7% of blindness is caused by cataracts. While the prevalence of blindness due to cataracts in the population aged 50 years and over in Indonesia is 1.9%. The estimated incidence of cataracts in Indonesia is 0.1% per year or every year among 1,000 people there is a new cataract sufferer. This study aims to determine the characteristics of senile cataracts in patients with diabetes mellitus. The design of this study is a Literature Review or literature review, Based on the results of the review, the characteristics of senile cataracts in patients with diabetes mellitus are concluded that: most patients suffer from cataracts in someone who is elderly, namely from 51 years to 60 years, in women more than men, in the cataract stage many immature stages are found, the length of suffering from DM is also a risk factor for cataracts and blood sugar levels are also one of the risk factors for cataracts.